Association Between Using Smartphone Dating Applications and Alcohol and Recreational Drug Use in Conjunction With Sexual Activities in College Students. (21st March 2017) - Choi, Edmond P. H.; Wong, Janet Y. H.; Lo, Herman H. M.; Wong, Wendy; Chio, Jasmine H. M.; Fong, Daniel Y. T.
ABSTRACT: Background : The association between using smartphone dating applications (apps) and substance use in conjunction with sexual activities was only examined in homosexual men. This association was poorly understood in heterosexual samples. Objective : To explore the association between using dating apps and alcohol, and use of recreational drug in conjunction with sexual activities in college students. Design : 666 students from four universities in Hong Kong were recruited in this cross-sectional study in the year 2015. Outcome measures included the use of dating apps, sexual history, and drug and alcohol use. Multivariable logistic regressions were employed. Results : The use of dating apps for more than 1 year was found to be associated with recreational drug use in conjunction with sexual activities (adjusted odds ratio: 7.23). Other risk factors of recreational drug use in conjunction with sexual activities included being bisexual/homosexual male, a smoker, and having one's first sexual intercourse at the age of less than 16 years. The use of dating apps was not a risk factor for alcohol consumption in conjunction with sexual activities. Risk factors for alcohol consumption in conjunction with sexual activities included being older, having monthly income more than HKD5, 000, and a smoker. Furthermore, risk factors for alcohol consumption in conjunction with the last sexual activity included currently being in a dating relationship, a smoker, and having sex with a casual partner. Conclusions : Using dating apps is an emerging risk factor of drug misuse. Interventions for practising safe sex and preventing drug use should be targeted at dating app users.